2018
DOI: 10.1111/napa.12116
|View full text |Cite
|
Sign up to set email alerts
|

“Service‐learning makes it real”

Abstract: At Minnesota State University, Mankato, the Anthropology Department pursued service‐learning as a means of educating and engaging diverse publics. An assessment of the service‐learning program began after it became clear that standard course evaluations provided an inadequate assessment of service‐learning's efficacy. We employed a mixed‐ method, multiperspective approach, combining interview data gathered from students, faculty, community partners, and program coordinators to complement existing archival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies reveal that this is the level of motivation and involvement that students participating in a SL project usually achieve [21,22]. This is so due to the level of prominence they play in the teaching-learning process of the specific population they work with, the opportunity to relate the theoretical content acquired in the classroom with practice in real educational contexts, the resolution of problems that they must address in those contexts or the cross-cutting attitudes and competencies they acquire during the process and which they could hardly acquire otherwise [23][24][25]. Motivation is directly related to one's personal goals, which are translated into different levels of commitment to the task that can predict the processes of students' achievement and results [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies reveal that this is the level of motivation and involvement that students participating in a SL project usually achieve [21,22]. This is so due to the level of prominence they play in the teaching-learning process of the specific population they work with, the opportunity to relate the theoretical content acquired in the classroom with practice in real educational contexts, the resolution of problems that they must address in those contexts or the cross-cutting attitudes and competencies they acquire during the process and which they could hardly acquire otherwise [23][24][25]. Motivation is directly related to one's personal goals, which are translated into different levels of commitment to the task that can predict the processes of students' achievement and results [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One assessment of a service-learning program at Minnesota State University includes projects with historical societies, a free clinic, Habitat for Humanity, and a leadership program for at-risk youth. The assessment found that students, faculty, and community partners appreciated the "realness" of projects, and that the experience also improved student comprehension and application of skills initially learned in the classroom (Schalage, Pajunen, and Brotherton 2018). Collaborative research, community projects, and other experiential learning techniques are valuable approaches in applied anthropology education.…”
Section: Flexibility In Teaching and Learning Anthropology And Preparing Students For Life After Collegementioning
confidence: 99%